Dynamic response prediction of prototype from scale-down model for I-core sandwich panels subjected to internal explosion. (April 2023) - Chen, Changhai; Liu, Ran; Han, Zhengjun; Cheng, Yuansheng
Highlights: A new prediction method from distortion scale-down model to prototype was proposed. Quasi-static pressure load was reasonably considered from the energy point of view. The proposed prediction method demonstrated high accuracy and good feasibility. The effects of TNT charge mass and its correction method were revealed. The effect of quasi-static pressure load on prediction accuracy was elucidated. Abstract: Cabin scale-down model experiments are an effective approach to investigate the dynamic response of I-core sandwich panels subjected to internal explosion. However, it is difficult to guarantee the complete geometrical similarity in terms of plate thickness for I-core sandwich panels between the scale-down model and prototype due to manufacturing process restriction and thickness specifications of commercially available plates. To resolve the above issue, a new and more reasonable dynamic response prediction method with high accuracy for prototype based on scale-down model test was proposed in the present work. The feasibility and accuracy of proposed prediction method were theoretically, experimentally, and numerically verified. The effects of TNT charge mass, correction method of TNT charge mass, and quasi-static pressure load were investigated. Results show that the proposed prediction method from the energy point of view has high accuracy and good feasibility when the plate thickness of scale-down model distorts. In the proposed approach, the TNT charge mass is corrected through specific impulse correction. Higher accuracy is gained by using the proposed prediction method in the case of internal explosion with large TNT charge mass. Directly correcting the TNT charge mass on the basis of geometrical similarity still underestimates the dynamic response of incomplete scale-down model when plate thickness distorts. It is not reasonable to ignore the effect of quasi-static pressure load, because the specific impulse of quasi-static pressure load is much larger than that of shock wave load. This work can provide practicable and accurate application guidance for the design of internal explosion scale-down model experiments for I-core sandwich panels.